The study of marketing opportunities for the use of the raw material of feverfew (Tanacetum parthenium L.) in the pharmacotherapy of musculoskeletal system diseases - Yevtushenko, O. M.; Ruban, O. A.; Velia, M. I.; Kovalevska , I. V. (Social Pharmacy in Health Care, 2024)
Aim. To form a modern idea of the market structure and trends in the consumption of drugs for the pharmacotherapy of rheumatoid arthritis, to determine the possible potential for use of plant raw material of feverfew (Tanacetum parthenium). Materials and methods. The study was conducted using the structural analysis, logical and graphical methods, and marketing analysis methods. Results. It was found that in the pre-war period the market for drugs affecting the musculoskeletal system developed quite vigorously – its growth rate in the period of 2020-2021 ranged from 16 to 29 % in natural units and from 20 to 30 % in monetary terms. According to the structure of producing countries, the market was significantly import-dependent. The market for synthetic drugs was quite saturated, represented by various dosage forms – tablets, powder for suspension, injection solutions (ampoules), granules, capsules, sachets, alcohol solutions, oil solutions, suppositories, oral suspensions, transdermal patches, gels, ointments. The research was conducted taking into account the study of marketing opportunities for the use of the raw material of Tanacetum parthenium in the pharmacotherapy of diseases of the musculoskeletal system since this raw material had certain advantages compared to synthetic analogs. It should be noted that the market of herbal medicines for the treatment of the musculoskeletal system diseases or the prevention of their manifestations is very limited and is represented by a minimum number of product items and one representative of the medicinal flora – Symphytum officinale. In addition, 90 % of the market for this group of drugs belongs to foreign manufacturers. Although research of the market for biological supplements indicates a certain demand for products based on the medicinal plant raw material. Conclusions. Based on the trends identified, we can state the positive development of the market for drugs that affect the musculoskeletal system, the prospects for the development of drugs based on the medicinal plant raw material, including Tanacetum parthenium.